Is allelochemical synthesis in Casuarina equisetifolia plantation related to litter microorganisms? - Xu, Zhixia; Zuo, Linzhi; Zhang, Yaqian; Huang, Rui; Li, Lei (Frontiers in Plant Science, 2022)
Productivity decline of Casuarina equisetifolia plantation and difficulty in natural regeneration remains a serious problem because of allelopathy. Previous studies have confirmed that 2,4-di-tert-butylphenol (2,4-DTBP) are the major allelochemicals of the C. equisetifolia litter exudates. The production of these allelochemicals may derive from decomposition of litter or from the litter endophyte and microorganisms adhering to litter surfaces. In the present study, we aimed to evaluate the correlation between allelochemicals in litter and endophytic and epiphytic fungi and bacteria from litter. A total of 100 fungi and 116 bacteria were isolated from the interior and surface of litter of different forest ages (young, half-mature, and mature plantation). Results showed that the fermentation broth of fungal genera Mycosphaerella sp. and Pestalotiopsis sp., and bacterial genera Bacillus amyloliquefaciens, Burkholderia-Paraburkholderia, and Pantoea ananatis had the strongest allelopathic effect on C. equisetifolia seeds. Allelochemicals, such as 2,4-DTBP and its analogs were identified in the fermentation broths of these microorganisms using GC/MS analysis. These results indicate that endophytic and epiphytic fungi and bacteria in litters are involved in the synthesis of allelochemicals of C. equisetifolia. To further determine the abundance of the allelopathic fungi and bacteria, Illumina MiSeq high-throughput sequencing was performed. The results showed that bacterial genera with strong allelopathic potential were mainly distributed in the young and half-mature plantation with low abundance, while the abundance of fungal genera Mycosphaerella sp. and Pestalotiopsis sp. were higher in the young and mature plantations. In particular, the abundance of Mycosphaerella sp. in the young and mature plantations were 501.20% and 192.63% higher than in the half-mature plantation, respectively. Overall, our study demonstrates that the litter fungi with higher abundance in the young and mature plantation were involved in the synthesis of the allelochemical 2,4-DTBP of C. equisetifolia. This finding may be important for understanding the relationship between autotoxicity and microorganism and clarifying the natural regeneration problem of C. equisetifolia.